1996
DOI: 10.2466/pms.1996.82.3.995
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Examination of the Factors Influencing the Origination, Continuation, and Cessation of Identification with Sports Teams

Abstract: Surn7nary.-While previous work had focused on the manner in which identification wich a sports team influences the reactions of spectators, research had yet to identdy those factors with the greatest amount of influence on identification. This article reports on an exploratory study designed to fill this void by idendying the factors involved in the origination, continuation, and cessarion of sports-team identification. Responses indicated that a wide variety of factors were perceived by fans to be important i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
124
4
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(137 citation statements)
references
References 8 publications
7
124
4
2
Order By: Relevance
“…Figure 1, the circle labelled A depicts the role of interpersonal attachments (e.g., friendship, family, or other relational groups) that socialise new consumers into the superordinate identity, subgroup identity, or both simultaneously. Previous research illustrates the crucial role that family and friendship groups play in the formation of attachment and identification (James, 2001;Spaaij & Anderson, 2010;Wann et al, 1996). Wann et al (1996) found that social factors were important in the origination of team identification.…”
Section: Relational Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1, the circle labelled A depicts the role of interpersonal attachments (e.g., friendship, family, or other relational groups) that socialise new consumers into the superordinate identity, subgroup identity, or both simultaneously. Previous research illustrates the crucial role that family and friendship groups play in the formation of attachment and identification (James, 2001;Spaaij & Anderson, 2010;Wann et al, 1996). Wann et al (1996) found that social factors were important in the origination of team identification.…”
Section: Relational Groupsmentioning
confidence: 99%
“…Previous research illustrates the crucial role that family and friendship groups play in the formation of attachment and identification (James, 2001;Spaaij & Anderson, 2010;Wann et al, 1996). Wann et al (1996) found that social factors were important in the origination of team identification. James (2001) found that parents -particularly fathers -played a crucial role in the development of their children's attitudes toward sport teams.…”
Section: Relational Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors suggest different team-related factors as constituents of team-fan identification, including previous successes, star players, geographical reasons, friends and peers become a fan, parents and family become a fan, logo, stadium and fame [34] successful season, managerial decisions, fame and tradition [24] success, style, color and players [35] symbolic relations (with players, color, logo or name of the team), socio-cultural relations, team victories, star players, sociological factors including social underdogs [36] Vicarious Achievement through relationships with team, players or coaches [37] successes, performance, tradition and stadium [6] identity attractiveness [10,30,38] self-definitional needs [10,17,18,30].…”
Section: Identificationmentioning
confidence: 99%
“…In addition, Wann, Tucker, and Schrader (1996) found there are some factors affecting the inauguration, maintenance, and termination of identification with sport teams. Of these factors, attachments to the players and the geographical reason (attachment to the community) are two of the most important factors for the continuation of identification with sport teams.…”
Section: Points Of Attachmentmentioning
confidence: 99%